Maternal pre-pregnancy body mass index and gestational weight gain on adverse birth outcomes in Chinese newborns: a retrospective study - Zhi Huang; Xia Tan; Jinlian Wang; Aiping Zhang (BMC, 2024)
Abstract Background Maternal and child health is an important measure of national well-being. This study further explored the individual and combined effects of maternal pre-pregnancy body mass index (BMI) and gestational weight gain (GWG) on adverse birth weight-related outcomes. Methods A retrospective study was carried out at a maternal and child health hospital from 2018 to 2021, and a total of 17,506 eligible women were invited to participate. The associations of pre-pregnancy BMI and GWG with adverse birth outcomes were examined by using restricted cubic spline regression and binary logistic regression. Results Pre-pregnancy BMI and GWG had non-linear associations with low birth weight and macrosomia. They were associated with an increased risk of macrosomia (Pre-pregnancy BMI for OR = 1.170, 95%CI:1.144 to 1.197, P < 0.001, and GWG for OR = 1.071, 95%CI:1.054 to 1.089, P < 0.001) and large for gestational age infant (LGA) (Pre-pregnancy BMI for OR = 1.125, 95%CI:1.111 to 1.141, P < 0.001, and GWG for OR = 1.045, 95%CI:1.036 to 1.054, P < 0.001). The high risk of low birth weight and preterm birth was observed among the group of women with inadequate GWG. The risks of macrosomia and LGA increased with pre-pregnancy BMI from low weight to overweight and obesity, and GWG from inadequate to overabundance, while small for gestational age infant was more prevalent in the low pre-pregnancy BMI group. Conclusions Pre-pregnancy BMI and GWG exhibited non-linear associations with low birth weight and macrosomia. The various combinations of pre-pregnancy BMI and GWG had different effects on adverse birth weight-related outcomes.